Infertility and physical activity: A cross-sectional study of women living in Yazd aged 20-49 yr, 2014-2015 - Masoud Mirzaei; Ph.D; Nasim Namiranian; Behnam Bagheri-Fahraji; Somaye Gholami (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Changes in the state of energy balance owing to changes in physical activity (PA) may affect the reproductive system. Objectives: the aim of this study was to assess the association between PA and infertility of women living in Yazd 2014 - 2015. Materials and Methods: The study method was analytical cross-sectional on the Yazd Health Study (YaHS) data which was conducted on 10,000 people. We studied 2,611 women (20 and 49 yrs old), living in Greater Yazd area. PA information was collected using a physical activity questionnaire (IPAQ) short form. The standardized instruments were used for anthropometrics measurement. Results: Totally 135 cases of infertility were documented. The overall prevalence of infertility was 4.73% (95% CI: 3.94-5.59%). The median of PA scores (METs) in women was 746.66 and 25-75% interquartile range was 361.25-1277.25. The relationship according to the Chi-square test between infertility and PA, as categorized variables, was significant (p = 0.015). It showed over 90% of those who suffered from infertility had a low or moderate PA. Conclusion: The results of our study showed that there is a significant relationship between infertility and PA level in women living in Greater Yazd area. Also, women with infertility had lower activity levels, consistent with most previous studies.Key words: Women, Infertility, Physical activity, Yazd, Iran.}